LEARNING TOOL DEVELOPMENT WITH THE PROBLEM BASED LEARNING (PBL) MODEL-ORIENTED MATHEMATICAL CRITICAL THINKING ABILITY - Restika Rahmadani; Sari Herlina (Mathematics Research and Education Journal, 2020)
This study aims to produce learning tools in the form of Learning Implementation Plans (RPP) and Student Worksheets (LKPD) with Problem Based Learning (PBL) oriented Mathematical Critical Thinking Ability which has been tested for validity. The type of research used is Development Research using a modified ADDIE development model, namely the Analysis, Design, Development, and Evaluation stages. Instruments and data collection techniques are in RPP and LKPD validation sheets by validating learning tools by 2 Mathematics Education Lecturers, FKIP UIR, and 2 Mathematics Subject Teachers. The data analysis technique used is data analysis of the validation results of learning devices using descriptive statistics. The results showed that the results of the RPP validity for each aspect were 84.13%, with a very valid validity level. Each validator was 84.84%, with a very valid validity level. In comparison, the LKPD validity results for each aspect were 84.59%, with a very valid validity level, and each validator is 84.42% with a very valid validity level. Based on the results of the development of these learning tools, a Learning Device with a Problem Based Learning (PBL) Model oriented to Mathematical Critical Thinking Skills on Quadrangular Material has been tested for validity